If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = x + 6y Reorder the terms: -3 + 4x = x + 6y Solving -3 + 4x = x + 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 4x + -1x = x + -1x + 6y Combine like terms: 4x + -1x = 3x -3 + 3x = x + -1x + 6y Combine like terms: x + -1x = 0 -3 + 3x = 0 + 6y -3 + 3x = 6y Add '3' to each side of the equation. -3 + 3 + 3x = 3 + 6y Combine like terms: -3 + 3 = 0 0 + 3x = 3 + 6y 3x = 3 + 6y Divide each side by '3'. x = 1 + 2y Simplifying x = 1 + 2y
| 2x-5/x-4+11/x-4 | | 4+x-5x=0 | | 12x+5=6x+25 | | 5x-9+2x=19 | | 6+5d=2d-4 | | 14-5y=50-4y | | 28=2(y-4)-8y | | 8x+y=52 | | c=f/0 | | 11a+6a-a= | | c=rw | | -(4x^3/y^2)^0 | | 9k^2-12k-1=0 | | t^2-20=176 | | -6x-4x=-30 | | 3x+2y=216 | | 5(v-5)-8v=-10 | | (cos)x=.3x | | (3-u)(3u-8)=0 | | 2p^2-20p+13=0 | | 12-(-39)-(27)= | | 3x+5x^1/2=28 | | sqrt(x)=-64 | | 1/5t-3=-17 | | x-8/3=-4 | | 1/2+1/2c-2 | | x^3-1728=0 | | x-98=68 | | 3=-21x | | x(x-6)=-9 | | n-3/4=-2,3/4 | | 2x^2-16=-3x^2-5x-2 |